Impacts of electronic invoicing in the portuguese healthcare sector: potential savings on accounts payable - Pereira, Filipa Gomes (2018)
The manual processes for exchanging commercial and financial documents between an entity and its suppliers create inefficiencies in the supply chain. However, there are electronic solutions able to eliminate errors and decrease the costs in accounting departments. This work aims to study the potential savings of migrating from manual to electronic invoicing process in accounts payable operations, on the Portuguese healthcare system. Besides invoices, other commercial documents are taking into account during this process: purchase orders and transport guides. There are considered three suppliers’ types: medicines and medical devices, utilities and services. The study includes seven healthcare entities belonging to Portuguese Health Service (Centro Hospitalar de Lisboa Central, Centro Hospitalar de Lisboa Norte, Centro Hospitalar de Lisboa Ocidental, Centro Hospitalar do Porto, Hospital Professor Doutor Fernando Fonseca, Centro Hospitalar de Trás-os-Montes e Alto Douto) and two service providers (Indra and Saphety). Data was collected by two different questionnaires, sent by electronic mail to each entity. In order to migrate to an electronic process for receiving invoices, it is needed an Electronic Data Interchange technology. The results show that the Ministry of Health is able to save around €2,435,249, considering the seven entities, in the first year of implementation. In a horizon of three years, the potential savings are €8,435,249. In addition, the usage of electronic data interchange allows the Ministry of Health to use a business intelligence technology and create policies with a higher degree of accuracy.